Invasion of epithelial mammalian cells by Paracoccidioides brasiliensis leads to cytoskeletal rearrangement and apoptosis of the host cell - Mendes-Giannini, Maria José Soares [UNESP]; Hanna, S. A.; Silva, J. L. M. da; Andreotti, P. F.; Vincenzi, L. R.; Benard, G.; Lenzi, H. L.; Soares, Christiane Pienna [UNESP] (Elsevier B.V., 2004)
Paracoccidioides brasiliensis (Pb) yeast cells can enter mammalian cells and probably manipulate the host cell environment to favor their own growth and survival. We studied the uptake of strain Pb 18 into A549 lung and Vero epithelial cells, with an emphasis on the repercussions in the cytoskeleton and the apoptosis of host cells. Cytoskeleton components of the host cells, such as actin and tubulin, were involved in the P. brasiliensis invasion process. Cytochalasin D and colchicine treatment substantially reduced invasion, indicating the functional participation of microfilaments (MFs) and microtubules (MTs) in this mechanism. Cytokeratin could also play a role in the P. brasiliensis interaction with the host. Gp43 was recognized by anti-actin and anti-cytokeratin antibodies, but not by anti-tubulin. The apoptosis induced by this fungus in infected epithelial cells was demonstrated by various techniques: TUNEL, DNA fragmentation and Bak and Bcl-2 immunocytochemical expression. DNA fragmentation was observed in infected cells but not in uninfected ones, by both TUNEL and gel electrophoresis methods. Moreover, Bcl-2 and Bak did not show any differences until 24 h after infection of cells, suggesting a competitive mechanism that allows persistence of infection. Overexpression of Bak was observed after 48 h, indicating the loss of competition between death and survival signals. In conclusion, the mechanisms of invasion of host cells, persistence within them, and the subsequent induction of apoptosis of such cells may explain the efficient dissemination of P. brasiliensis. (C) 2004 Published by Elsevier SAS.
Keywords: Paracoccidioides brasiliensis; cytoskeleton; invasion; apoptosis; host-cell biology